Differential Subordination For Meromorphic Functions Defined By A Linear Operator. - M. Ali, Rosihan; Ravichandran, V. (© SAS International Publications, 2004)
By making use of a linear operator that is defined by means of the Hadamard product (or convolution), we investigate the properties of a certain family of meromorphically multivalent functions.